Indicadores antropométricos do estado nutricional de pré-escolares em Araraquara, SP - Foschini, Ana Lígia Rozato [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (My University, 2010)
The purpose of this study was to examine the anthropometric indicators of nutritional status in preschool children from public schools in the city of Araraquara, SP. The sample was selected in a probabilistic stratifi ed way and its size was set by a fi nite population sampling. The anthropometric indicators of the weight/ height (WHZ), height/age (HAZ), weight/age (WAZ) and body mass index (BMIZ) were calculated. The classifi cation of the nutritional status was accomplished according to the recommendation of the World Health Organization. 26 The education and economic level of the household head were evaluated by completing a questionnaire proposed by ANEP. 2 Pilot study was conducted to assess the intraexaminer agreement. A statistical descriptive analysis was accomplished and the associations of interest were made by applying the chi-square test (2 ). A signifi cance level of 5% was used. It was observed that 8.64% of preschool children were wasted, with predominance of the girls (p=0.013). The prevalence of low weight was 1.66% and 1.00% of the children were stunted with signifi cant association with the number of people living in the house. Of the preschoolers 38.37% were excess weighted. The prevalence of obesity was 15.78%. There was a greater number of girls with obesity and a greater number of boys with excess weight (p=0.049). The prevalence of excess weight was high in preschool children in this population and it should be considered in the planning of public guidelines.

Realizou-se este trabalho para estudar os indicadores antropométricos do estado nutricional de pré- escolares matriculados na rede pública de ensino do município de Araraquara, SP. A amostra foi selecionada de forma probabilística estratifi cada e seu tamanho estabelecido por processo de amostragem para população fi nita. Foi realizado o cálculo dos indicadores antropométricos (em escore-z) peso para altura, altura para idade, peso para idade e Índice de Massa Corpórea. A classifi cação do estado nutricional foi realizada segundo a população de referência da Organização Mundial de Saúde. 26 O nível econômico e escolaridade do chefe de família foram avaliados por meio do questionário proposto pela ANEP. 2 Realizou-se estudo piloto para aferir a concordância intra-examinador. Os dados foram analisados por meio de estatística descritiva e as associações foram realizadas com o teste de qui-quadrado (2 ), adotando-se um nível de signifi cância de 5%. Observou-se prevalência de desnutrição aguda de 8,64% com predomínio do sexo feminino (p=0,013). A prevalência de baixo peso encontrada foi de 1,66% e de desnutrição crônica foi de 1,00% com associação signifi cativa com o número de pessoas residentes no domicílio. Dos pré-escolares, 38,37% apresentaram excesso de peso. A prevalência de obesidade foi de 15,78%. Observou-se maior número de crianças do sexo feminino obesas e maior número de meninos com sobrepeso (p=0,049). Conclui-se que a prevalência de pré-escolares com excesso de peso é alta nesta população o que deve ser considerado em planejamentos de ações públicas.
Anthropometric indicators of nutritional status in preschool children in Araraquara, SP – Brazil
Keywords: Nutritional state; Anthropometry; Child preschool; Estado nutricional; Antropometria; Pré-escolares